Biological Baseline of Joint Self-Repair Procedures - Di Nicola, Valerio; Pierpaoli, Walter (Current Aging Science, 2013)
Gel-Repairer is a biomaterial composed of Polydeoxyribonucleotides (Pdrn), Heat Shock Proteins (Hsps) and a thickening substance. It works as a local mesenchymal stem cells (MSCs) stimulator, finally generating connective tissue renewal. Our research is within the field of regenerative medicine and has historically built its foundation from the studies carried out on non-vital amnion and placental membranes. Our end point is the activation and stimulation of the local mesenchymal stem cells (MSCs) for the structural recovery of the joint involved in the degenerative process. Since 2003, we have been applying the Gel Repairer over morethan 1200 patients, most of them elderly, affected by Degenerative Joint Disease (DJD). After 10 years of clinical experience, the results are really impressive, including the absence of toxicity, adverse reactions or side effects. Our clinical findings allowed the presentation of a clinical preliminary study performed on a large group of patients from 2003 to 2009 and recently published [1]. The following article is aimed at looking into the mechanism of action of the Joint Self-Repair procedure; furthermore some new technical opportunities are presented on tissue engineering advances in this fast evolving sector.
Keywords: Growth Factors (GFs)